Nailfold capillary abnormalities as indicators of diabetic nephropathy progression: a cross-sectional study in type 2 diabetes - Po-Chi Hsu; Pei-Yung Liao; Ssu-Wei Huang; Hen-Hong Chang; John Y. Chiang; Lun-Chien Lo (Annals of Medicine)
Background Type 2 diabetes mellitus (DM) leads to chronic hyperglycemia and microvascular complications, including diabetic nephropathy (DN). Nailfold videocapillaroscopy (NVC) is a non-invasive method for assessing the microvascular abnormalities and may aid in early DN detection. This study investigates the correlation between DN and nailfold capillary abnormalities in type 2 DM.Methods This prospective cross-sectional study involved 453 participants with type 2 DM, divided into 3 groups based on estimated glomerular filtration rate (eGFR) or albumin-to-creatinine (A/C) ratio. Chronic kidney disease (CKD) risk categories based on the 2012 Kidney Disease Improving Global Outcomes (KDIGO) guidelines. Participants underwent structured interviews, clinical assessments, and laboratory tests. NVC was performed to assess capillary morphology, distribution, density, and blood flow.Results Significant differences in NVC measurements were observed across eGFR groups, with higher NVC scores and more severe capillary abnormalities noted in lower eGFR groups. The ‘comma-like’ capillary distribution pattern (23.08%, p = 0.016), more ratio of ramified capillaries (p = 0.0137) were observed in the eGFR <30 ml/min/1.73m2 group. Reduced fundus transparency (p = 0.0015) and impaired visibility of the sub-venous plexus (p = 0.0016) were noted in the lower eGFR groups. Capillary lengths, both input and mean, were shorter in the A/C ratio > 300 mg/g group (p = 0.0382 and p = 0.0478, respectively). The NVC score was higher in the A/C ratio > 300 mg/g groups (p = 0.0028).Conclusion Nailfold capillary abnormalities correlate with DN severity, indicating their potential as a non-invasive biomarker for early DN detection and monitoring in type 2 DM.